Self-rated health among undocumented and newly regularized migrants in Geneva: a cross-sectional study - Julien Fakhoury; Claudine Burton-Jeangros; Idris Guessous; Liala Consoli; Aline Duvoisin; Yves Jackson (BMC, 2021)
Abstract Background In Europe, knowledge about the social determinants of health among undocumented migrants is scarce. The canton of Geneva, Switzerland, implemented in 2017-2018 a pilot public policy aiming at regularizing undocumented migrants. We sought to test for associations between self-rated health, proven eligibility for residence status regularization and social and economic integration. Methods This paper reports data from the first wave of the Parchemins Study, a prospective study whose aim is to investigate the effect of residence status regularization on undocumented migrants' living conditions and health. The convenience sample included undocumented migrants living in Geneva for at least 3 years. We categorized them into those who were in the process of receiving or had just been granted a residence permit (eligible or newly regularized) and those who had not applied or were ineligible for regularization (undocumented). We conducted multivariate regression analyses to determine factors associated with better self-rated health, i.e., with excellent/very good vs. good/fair/poor self-rated health. Among these factors, measures of integration, social support and economic resources were included. Results Of the 437 participants, 202 (46%) belonged to the eligible or newly regularized group. This group reported better health more frequently than the undocumented group (44.6% versus 28.9%, p-value < .001), but the association was no longer significant after adjustment for social support and economic factors (odds ratio (OR): 1.12; 95% confidence interval (CI): 0.67-1.87). Overall, better health was associated with larger social networks (OR: 1.66; 95% CI: 1.04-2.64). This association remained significant even after adjusting for health-related variables. Conclusion At the onset of the regularization program, access to regularization was not associated with better self-rated health. Policies aiming at favouring undocumented migrants' inclusion and engagement in social networks may promote better health. Future research should investigate long-term effects of residence status regularization on self-rated health.